Synthesis of high crystallinity biphasic calcium phosphates/gold nanoparticles composites by solution combustion method with antimicrobial response (2022)
ABSTRACT: Calcium phosphates are biomaterials widely used in bone tissue engineering. In recent years, the alternative of obtaining these materials with antimicrobial properties, has been explored due to the multiple advantages that this would imply in the design of devices or implants that prevent the failure of these associated with bacterial colonization. The goal of the present work was obtaining gold nanoparticles supported on biphasic calcium phosphates (BCPs) with high crystallinity by one-step solution combustion technique, and with antimicrobial response, a fact that can significantly reduce the production cost of these materials. X-ray diffractograms (XRD) showed that prepared powders have high crystallinity owing to high temperatures during the combustion reaction, also Rietveld refinement showed that the inclusion of gold nanoparticles (AuNPs) influenced the phases’ ratio obtained. Furthermore, scanning electron microscopy (SEM) showed agglomeration of particles with morphologies with shape tending to be equigranular, while the presence of AuNPs was corroborated by transmission electron microscopy (TEM). All samples that were obtained in a single step, by solution combustion, showed antimicrobial behavior validated through the inhibition halos, whereas particles subjected to thermal treatment lost their antimicrobial response.